2022
DOI: 10.5545/sv-jme.2022.184
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Experimental Research as a Contribution to the Development of an Experimental Model of Rolling Bearing Vibrations

Abstract: The influence of rolling bearing contamination on the level of generated vibrations is ignored in many cases. The influence is clearly visible in the theoretical and experimental works on the mathematical modelling of rolling bearing vibration. The authors of the most recent works in this field use substantial simplifications, often ignoring the presence of solid particles between the rolling bearing mating surfaces. However, bearing in mind the continuous improvement of the rolling bearings production process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, the rolling bearing vibration big data caused by variable working conditions and shock excitation have typical nonlinear non-stationary complex characteristics [3] and [4], which makes the existing signal processing techniques, such as timedomain statistical analysis [5] and [6], frequencydomain spectral analysis [7] and [8], short-time Fourier transform [9], wavelet analysis [10] and [11], Hilbert-Huang transform (HHT) [12], variational mode decomposition (VMD) [13], difficult to extract fault features adaptively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rolling bearing vibration big data caused by variable working conditions and shock excitation have typical nonlinear non-stationary complex characteristics [3] and [4], which makes the existing signal processing techniques, such as timedomain statistical analysis [5] and [6], frequencydomain spectral analysis [7] and [8], short-time Fourier transform [9], wavelet analysis [10] and [11], Hilbert-Huang transform (HHT) [12], variational mode decomposition (VMD) [13], difficult to extract fault features adaptively.…”
Section: Introductionmentioning
confidence: 99%
“…Strojniški vestnik -Journal of Mechanical Engineering 69(2023)[5][6][261][262][263][264][265][266][267][268][269][270][271][272][273][274] …”
mentioning
confidence: 99%
“…The results indicated that both textured surfaces could reduce the high-frequency screaming noise of the friction system. Wrzochal et al [23] pointed out that the cleanliness of bearings is a key factor to determine whether rolling bearings meet the quality requirements. Chernets et al [24] proposed a computational method to solve the plane contact problem of elastic theory to determine the contact strength and tribological durability of plain bearings.…”
Section: Introductionmentioning
confidence: 99%